Incidence of inflammatory bowel disease in patients with ankylosing spondylitis - Lai, Shih-Wei; Kuo, Yu-Hung; Liao, Kuan-Fu (Annals of the rheumatic diseases, 2021)
The association between ankylosing spondylitis and other diseases has been extensively assessed.1 2 Recently a cohort study conducted by Schreiber et al published in Annals of the Rheumatic Diseases found that the new-onset cases of inflammatory bowel disease were uncommon in patients with ankylosing spondylitis on secukinumab therapy (1.13%, 9/794).3 In order to examine the association between ankylosing spondylitis and inflammatory bowel disease in a different country, a preliminary cohort study was undertaken using the 2005–2012 database of the Taiwan National Health Insurance Programme with 23 million residents living in Taiwan.4 Subjects ages 20–84 with a new diagnosis of ankylosing spondylitis were identified as the ankylosing spondylitis group (International Classification of Diseases, Ninth Revision code (ICD-9 code 720.0)). Table 1 presents that the overall incidence of inflammatory bowel disease was lower in the ankylosing spondylitis group than in the non-ankylosing spondylitis group, but without reaching statistical significance (1.41 vs 1.79 per 1000 person-years, incidence rate ratio 0.79, 95% CI 0.48 to 1.28; p=0.332). Incidence rates of inflammatory bowel disease in patients with psoriasis, psoriatic arthritis and ankylosing spondylitis treated with secukinumab: a retrospective analysis of pooled data from 21 clinical trials.